Orbital and Ocular Adnexal Lymphomas: A Retrospective Single Center Study - Astan İbayev; Altan Özcan; Burak Ulaş (Acta Medica Alanya)
Aim: To evaluate and present the clinical and histopathologic features of patients with orbital and adnexal lymphoma.Methods: Eight patients who had histologically proven orbital and adnexal lymphoma between 2011 and 2021 were evaluated retrospectively. The clinical appearance, age, sex, imaging, tumor location, treatment methods, pathologic diagnosis, and systemic features of the patients were obtained from patient files.Results: The mean age of the patients was 59.1 (range, 42-79) years. Six of the patients were male and two were female. Painless mass and orbital swelling were the most common first signs and symptoms in the patients. The magnetic resonance imaging findings demonstrated unilateral involvement in six patients and bilateral involvement in two patients. Intraorbital location in three patients (behind the orbital septum), lid location in two patients (eyelids in front of the orbital septum), conjunctival involvement in one patient, and lacrimal gland involvement in two patients were detected. All cases were reported as non-Hodgkin B-cell lymphoma [primary extranodal marginal lymphoma of the mucosa-associated lymphoid tissue (n=5), diffuse large B-cell lymphoma (n=2), follicular lymphoma (n=1)].Conclusion: Orbital lymphomas can be seen more frequently among orbital tumors and clinical findings vary according to the location in the orbit. Ophthalmologists should be attentive to orbital swellings and consider orbital and ocular adnexal lymphomas among differential diagnoses.